Analysis of tea consumption of blackberry leaves on bone morphology and biomechanics of ovariectomized rats (Research, Society and Development, 2020)
The main objective of the study was to evaluate the effects of blackberry leaf tea on bone morphological and biomechanical parameters in ovariectomized rats. For this purpose, an experimental study was conducted with rats of the Wistar lineage, divided into four experimental groups, with or without ovaries (n=32), who were offered filtered water ad libitum or tea (form of infusion) of the leaves of Morus Nigra L. After 60 days of experimentation, the right femurs were removed and subjected to analysis of morphological and biomechanical properties. As a methodology, during the experiment the animals gained weight through a diet based on consumption of solid components (feed) and liquids (tea or water), within the few standards for rodents. The consumption of blackberry leaf tea revealed effects on bone morphological properties and decreased bone resistance in oophorectomized rats. The offer of Morus Nigra L. leaf tea had positive effects on the morphological and biomechanical properties of the femurs, suggesting greater bone resistance in the group of non-ovariectomized rats.